Des femmes écrivent l’histoire des femmes au milieu du XIXe siècle : représentations, interprétations - Isabelle Ernot (Genre & Histoire)
In the early 1980s the historiographic project behind women's history argued for the need to rewrite history or at the least to shake up exising discourses. This article addresses the difficult achievement of this project through an analysis of earlier writings by women historians/femmes de lettres who forged representations concerning the similitude of the sexes in the mid-nineteenth century. These cultural sources are used to illuminate the context within which they emerged and to question social and political history. Their interpretation highlights the deterioration of French women position at mid-century and thus challenges the  accuracy and the resistance of a dominant historical discourse that emphasizes the continuous progress of democracy in France.